1987
DOI: 10.1079/bjn19870104
|View full text |Cite
|
Sign up to set email alerts
|

Intra-individual variability and measurement noise in estimates of energy expenditure by whole body indirect calorimetry

Abstract: 1. Four men were each studied continuously over 12 d in a whole-body calorimeter. Dietary intake and daily activities were kept constant throughout the study. 2. Day-to-day coefficients of variation in energy expenditure within subjects were found to be 1.97% over 24 h, 5.93% during basal metabolic rate measurement, 2.40% overnight and 3.22% in exercise. 3. The contribution of measurement system noise to the observed variability was analysed and shown to be generally small. The source of this noise was conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 4 publications
6
39
0
Order By: Relevance
“…11 Whereas the acute thermogenic effect increases EE above baseline the lower chronic dose of sibutramine did not raise EE but did have a desired effect of disinhibiting the normal reduction in EE seen with decreasing energy intake and weight loss. The within subject coef®cient of variation for 24-h EE is fully comparable with that of other studies 13,17,20 and the effect found in the present study is very similar to the results reported by Astrup et al, who found that the decrease in 24-h EE was 3 ± 5% less after eight weeks of treatment with ephedrineacaffeine compared with placebo. 21 We observed that sleeping EE was slightly higher in the sibutramine group than the placebo group after 8 weeks.…”
Section: Discussionsupporting
confidence: 82%
“…11 Whereas the acute thermogenic effect increases EE above baseline the lower chronic dose of sibutramine did not raise EE but did have a desired effect of disinhibiting the normal reduction in EE seen with decreasing energy intake and weight loss. The within subject coef®cient of variation for 24-h EE is fully comparable with that of other studies 13,17,20 and the effect found in the present study is very similar to the results reported by Astrup et al, who found that the decrease in 24-h EE was 3 ± 5% less after eight weeks of treatment with ephedrineacaffeine compared with placebo. 21 We observed that sleeping EE was slightly higher in the sibutramine group than the placebo group after 8 weeks.…”
Section: Discussionsupporting
confidence: 82%
“…Similar results were observed by others (Table 4; Murgatroyd et al 1987;Fredrix et al 1990;Rieper et al 1993;Figueroa-Colon et al 1996;Ventham & Reilly, 1999). Discrepancies could be due to differences in protocol, methodology and study population.…”
Section: Discussionsupporting
confidence: 77%
“…1995), acute weight-loss (Jebb et al 1991) or pregnancy . Measurements of energy expenditure can be made with an accuracy of f 1 % over periods as short as 1 h, but potentially lasting for many days, to the limit of subject tolerance (Murgatroyd et al 1987).…”
Section: Metabolismmentioning
confidence: 99%